The combination of demulsification-flotation processes for separating dissolved oil in gum-rosin industry wastewater - Prayitno; Rulianah Sri; Sa’diyah Khalimatus; Dewajani Heny; Ramdhana Rucita (E3S Web of Conferences)
Wastewater produced from the gum-rosin and turpentine production process at the INHUTANI V factory contains dissolved oils (turpentine oil, pine resin, and acidic compounds). The agitation followed by the sedimentation process has not been effective in reducing dissolved oil, thus disrupting processing at the wastewater treatment plant (WWTP). This research aimed to analyze the separation of dissolved oils in wastewater using the demulsification and flotation processes. The experiment was carried out by adding demulsifiers at various dosage variations and stirring at various velocities. The variables used in the research include demulsifier dosage (2%, 4%, 6%, and 10% volume), stirring velocity (100 rpm, 120 rpm, and 130 rpm), and flotation time (10, 15, and 20 minutes). The parameters analyzed include non-volatile, and turbidity. The results of the study showed that at a demulsifier dose of 10%, a stirring velocity of 120 rpm, and a flotation time of 20 minutes, there was a decrease in the maximum concentration of non-volatile and turbidity of 87% and 92%, respectively.